Lying beside you - Robotham, Michael, 1960- (New York, NY : Pocket Books, an imprint of Simon & Schuster, LLC, 2024)
If I could tell you one thing about my brother, it would be this. Two days after his nineteenth birthday, he killed our parents and twin sisters because he heard voices in his head. As defining events go, nothing else comes close for Elias, or for me.
"Originally published in Great Britain in 2022 by Sphere"--Title page verso.
Keywords: Forensic psychologists -- Fiction; Psychologists -- Fiction; Murder -- Fiction; Missing persons -- Fiction; Brothers -- Fiction; England -- Fiction; Thrillers (fiction.); Detective and mystery fiction